Maintenance of a seismic network in Bangladesh and an initial earthquake catalog - Syed Idros Abdul Rahman (2021)
Bangladesh is a densely populated country located on the north-eastern side of the India-Eurasia collision zone. The eastern half of the country is underlain by the seismically active Chittagong-Myanmar Fold and Thrust Belt, which forms the accretionary prism associated with the eastward-subducting Indian Plate, and is bordered to the north by the Dauki thrust fault, which bounds the southern margin of the actively rising Shillong Plateau. Two great earthquakes occurred here in 1897 (~Mw8.0) and 1762 (~Mw8.5). The seismic hazard in this region is poorly constrained due to questions about slip partitioning between the frontal and splay faults of the fold and thrust belt, whether faults will eventually slip at seismic speeds, and how shaking will be amplified and/or attenuated by the thick sedimentary cover. Seismic monitoring of the region can help to address these questions. In 2016, a collaborative effort between the Earth Observatory of Singapore and Dhaka University led to the installation of a network of 22 Lennartz 1-Hz (Short-period) and 6 Trillium Compact 120-s (Broadband) seismometer stations along the north-eastern (Sylhet region) and south-eastern (Chittagong region) parts of Bangladesh. The aim of this network is to monitor seismicity and to develop a better understanding of the subsurface structure in the region. This network has been actively running for over 4 years. The stations are spaced about 15 to 30 km apart, and are installed in either outdoor shallow vaults, or in above ground indoor locations on solid foundations, depending on local conditions. The stations are visited every 3 to 5 months for data collection, as well as repair and maintenance work. Here we discuss challenges faced and overcome during the deployment associated with environmental conditions (soil, plant growth, monsoon flooding, soil erosion, and cyclones) as well as arising from human and wildlife interference, political instability, and the COVID pandemic. We present various solutions that were implemented to mitigate or eradicate these problems. We have derived a preliminary catalog of earthquake locations consisting of >1100 events, and also detected >130 teleseismic events; event locations are currently being refined. Our data will provide a better understanding of the seismic activity and subsurface geology of the region.